Clinical prognostic factors for central neurocytoma and subgroup analysis of different treatment measures: A SEER database-based retrospective analysis from 2003 to 2019 - Zhang, Zibin; Yu, Jianbo; Zhang, Chao; Pang, Xiaojun; Wei, Yuyu; Lv, Qingping; Chen, Huai; Jin, Xuhong; Zhan, Renya (Frontiers in Oncology, 2023)
Purpose The study aimed to identify clinical prognostic factors affecting overall survival (OS) in patients with central neurocytoma (CN) and to determine independent prognostic factors in the subgroups of different treatment modalities using a retrospective analysis based on the SEER database from 2003 to 2019. Materials and methods Data regarding patients with CN, including basic clinical characteristics, treatment measures, and prognosis follow-up, were extracted from the SEER database. The prognostic variables for all patients were assessed using log-rank test as well as univariate and multivariate analyses based on the Cox proportional hazards model. The same statistical methods were used for analysis in different subgroups of gross total resection (GTR), subtotal resection (STR), no surgery, radiotherapy (RT), and no RT. Results In total, 413 patients were enrolled in this study. Tumor size, primary site surgery, and RT were independent prognostic factors in all patients with CN. In subgroup analyses, RT was not an independent prognostic factor in patients with GTR. However, sex and race were independent prognostic factors in patients with STR. Additionally, tumor size was an independent prognostic factor in patients who did not undergo surgery. Furthermore, sex and primary site were independent prognostic factors in patients who received RT. Size and primary site surgery were independent prognostic factors in patients without RT. Conclusion In our study, patients with small tumors or GTR or those who did not receive RT showed a better prognosis. GTR was the preferred treatment for CN. RT was not recommended for patients after GTR. Men and African American showed certain advantages after STR surgery. Tumors with a size of >4 cm were recommended for active treatment. In the RT subgroup, patients with tumors outside the ventricle or women had a poorer prognosis than those with tumors within the ventricle or men, respectively. These findings will help clinicians and patients understand the treatment and prognosis of CN visually and intuitively.